Pendampingan Penyusunan Rencana Gerakan Peduli dan Berbudaya Lingkungan Hidup di Sekolah (PBLHS) untuk Mendukung Implementasi Sekolah Adiwiyata Nasional di MI Miftahul Ulum Gresik - Warju Warju; Sudirman Rizki Ariyanto; Susi Tri Umaroh; Muhammad Syahrul Anwari; Rafli Irmansah; Farzana Syazwanasyah Ilyasa Shafa (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2026)
One strategic effort to implement education for sustainable development is through the School Environmental Care and Culture Movement, known in Indonesia as Gerakan Peduli dan Berbudaya Lingkungan Hidup di Sekolah (PBLHS), formerly the Adiwiyata program. This community service program aimed to assist teachers at MI Miftahul Ulum Gresik in preparing a four-year PBLHS action plan, an annual PBLHS action plan, and lesson plans integrated with environmental education. The integration focused on global, local/regional, and school-based environmental issues to support the school’s readiness for the 2025 National Adiwiyata School Candidate selection. The specific target of this program was to improve teachers’ competence in developing lesson plans integrated with environmental education in accordance with Law No. 32 of 2009 on Environmental Protection and Management, Minister of Environment and Forestry Regulation No. P.52/MENLHK/SETJEN/KUM.1/9/2019 on the PBLHS Movement, and Regulation No. P.53/MENLHK/SETJEN/KUM.1/9/2019 on the Adiwiyata Award. The program was conducted through direct education and training consisting of five stages: preparation, implementation, evaluation, reporting, and dissemination. The preparation stage included needs assessment, development of presentation materials, and preparation of training equipment. The implementation stage involved material delivery and guided practice in preparing PBLHS planning documents and environmentally integrated lesson plans. Evaluation was carried out by reviewing the lesson plan products and collecting participants’ feedback through questionnaires. The results of this community service program included a four-year PBLHS action plan, an annual PBLHS action plan, and one lesson plan integrated with environmental aspects based on global, local/regional, and school-level issues.